Morphological and Molecular Analyses ofSimulium rufibasis(Diptera: Simuliidae) in Thailand - Takaoka, Hiroyuki; Srisuka, Wichai; Low, Van Lun; Saeung, Atiporn (Oxford University Press, 2018)
A man-biting black fly species so far regarded as Simulium rufibasis Brunetti in Thailand was morphologically analyzed. It was found to be almost indistinguishable in the female from S. rufibasis sensu stricto but distinguishable in the male by the slender fore basitarsus and abdominal segments 2, 6, and 7 each with a pair of shiny dorsolateral patches, and in the pupa by the absence of spine-combs on abdominal segment 7 and terminal hooks on segment 9. It is described as a new species, Simulium tenebrosum. Taxonomic notes are given to separate it from all 11 known species of the S. rufibasis subgroup of the Simulium (Simulium) tuberosum species-group. An analysis of the COI gene sequences shows that this new species is distantly separated from the closely related species. © The Author(s) 2018. Published by Oxford University Press on behalf of Entomological Society of America. All rights reserved.